Estimator and Controller Design for a Didactic Liquid Level system by System Identification Approach - Kamarudin, Muhammad Nizam; Md Rozali, Sahazati (2010)
This manuscript is a piece of report on the identification of Didactic Liquid Level Systems. The term didactic is used as to enlighten the purpose of proto-typing liquid level system for educational use. A liquid level system with unknown mathematical characteristic is identified using ARX (Auto-Regressive with Exogenous Input) model. The determination of such system, on the basis of experimental data is conducted to obtain the discrete transfer function as well as state space representation of it. The identification process which exploits the advantage of linear parametric ARX gives beneficial information such as correlation, best fit and poles-zeros location. The Linear Quadratic Regulator (LQR) is tested for such liquid level system before the estimator is designed. Literal analysis of the estimator performance is conducted as a preliminary insight to the next investigation on the self tuning Proportional – Integral – derivative (PID) algorithm